2011
DOI: 10.1177/0265407510397988
|View full text |Cite
|
Sign up to set email alerts
|

A dyadic approach to the study of romantic attachment, dyadic empathy, and psychological partner aggression

Abstract: This study examined the intrapersonal, dyadic, and mediational relationships underlying romantic attachment (Experiences in Close Relationships), dyadic empathy (Interpersonal Reactivity Index for Couples), and psychological partner aggression (Revised Conflict Tactics Scales) in 193 community-based couples. In women, attachment insecurity predicted lower dyadic empathy and greater psychological aggression. In men, attachment insecurity predicted lower perspective taking, higher empathic concern, and greater p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 76 publications
(135 reference statements)
10
86
3
4
Order By: Relevance
“…This study supports the more recent literature suggesting that violence by an intimate partner is not strictly a male-to-female phenomenon but a human phenomenon (Carmo, Grams, & Magalhaes 2011;Cho, 2012;Péloquin et al, 2011;Swan & Snow, 2003). That women and men in the present study report equal levels of psychological and (physical) IPV is at first sight deviant from the majority of research on IPV victimization.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study supports the more recent literature suggesting that violence by an intimate partner is not strictly a male-to-female phenomenon but a human phenomenon (Carmo, Grams, & Magalhaes 2011;Cho, 2012;Péloquin et al, 2011;Swan & Snow, 2003). That women and men in the present study report equal levels of psychological and (physical) IPV is at first sight deviant from the majority of research on IPV victimization.…”
Section: Discussionsupporting
confidence: 82%
“…Notwithstanding these aforementioned difficulties, recent studies have noted the importance of integrating psychological aggression in IPV research as it is more prevalent, often a precursor of physical IPV, and may be more harmful than physical IPV (Follingstad, 2007;Follingstad & Edmundson, 2010;Krug et al, 2002;Péloquin, Lafontaine, & Brassard, 2011;Romans et al, 2007). Therefore, we hypothesized that in the present study psychological violence would also be more prevalent than both physical and sexual IPV (hypothesis 2) Individual Well-Being Experiences with IPV undermine the individual well-being of victims (e.g., Afifi et al, 2009).…”
Section: Prevalence Research On Intimate Partner Violencementioning
confidence: 99%
“…These findings are congruent with past research findings (Hickman, Jaycox, & Aronoff, 2004;Péloquin, Lafontaine, & Brassard, 2011;Straus et al, 1996) assault perpetration than males, but males reported higher sexual coercion perpetration than females. This gender difference might reflect Thai society's thoughts and beliefs surrounding sexual issues in which females are taught to be more inhibited and more reserved when talking about sex in public.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Orcutt et al (2005) reported that females who had a high degree of anxious attachment and a low degree of avoidant attachment were prone to perpetrate their partners more than those who had high degrees of both attachment styles. In addition, Péloquin et al (2011) also found that avoidant attachment could predict perpetration in females, but that this was not indicative of males.…”
Section: Discussionmentioning
confidence: 97%
“…Less avoidant men and women reported being more sensitive to their partner's distress cues; this in turn was related to their partner's sexual satisfaction. Avoidant individuals have previously been found to feel less empathy toward their partners (Péloquin, Lafontaine, & Brassard, 2011) and to ignore distress-related cues (Mikulincer & Florian, 2001). A person's tendency to be sensitive to a partner's emotional needs and cues of distress likely transfers to the sexual sphere, heightening sensitivity to a partner's sexual needs and preferences.…”
Section: Discussionmentioning
confidence: 99%